A estética do silêncio em A Paixão segundo G.H., de Clarice Lispector - Fávaro, Karina Baldo (2012)
The study entitled The esthetics of silence in A Paixão segundo G.H. aims to analyze the esthetic meaning of silence and its forms of representation. The study takes into account the fictional expedients of silence that unfold by means of otherness, temporal plan of work and the extinction of the subject matter. The passion of G. H. is permeated by the process of depersonalization, denouncing the experiment of the author with the language. The dramatic struggle between speech and language is spread by the difficulty of the report and its experience markedly epiphanic transgresses what is really meant to say. On her work, the image built of an assumed reader, makes him a partner of the instability of the narrator, mistrusting her own narrative. This procedure makes the word evil and sadistic because it destabilizes who has participated in the trajectory of GH, experiencing her passion